Globalisasi dan Penerimaan LGBTQ+ di ASEAN: Studi Kasus Budaya Boys’ Love di Thailand - Yasmin Nur Habibah; Januar Aditya Pratama; Mesagus Muhammad Iqbal (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2021)
The global push for LGBTQ + still faces many challenges, especially in Eastern regions, and Southeast Asia is no exception. Most national laws identify LGBTQ + people as a psychiatric disorder who deserve certain penalties. This phenomenon certainly has an impact on how society accepts these people socially. According to research conducted by the Pew Research Center, public acceptance of the LGBTQ + movement has increased since 2002, even in countries that can be described as quite conservative, Thailand is no exception. The culture which became an industrial asset, namely ladyboys, is also an indication of Thailand's acceptance of the LGBTQ+ movement. Now, since 2018, the Thai film industry with the theme Boys' Love (BL) has received a lot of support from film and drama lovers, especially in ASEAN countries. In this paper, we will discuss the development of BL culture in Thailand, which then has the potential to have an impact on public acceptance of ASEAN member countries regarding LGBTQ + issues. Based on the analysis with the queer theory perspective, it is found that BL culture—which is often seen as the impact of socio-cultural globalization—can be a force that